Status of Fisheries Resource Utilization with Ecosystem Approach (EAFM) in Lubuk Larangan Area, Teluk Paman Timur Village, Kampar Kiri District, Kampar Regency, Riau - Pandera, Cici; Prianto, Eko; Purwanto, Eko (Jurnal Perikanan dan Kelautan, 2025)
The utilization of fisheries resources in Teluk Paman Timur Village is closely related to local customs. The rule of lubuk larangan limits the community's activities, where the community is prohibited from fishing until a specific time limit. However, changes in river flow have led to sedimentation and siltation, which affects the effectiveness of this lubuk larangan. This study aimed to assess the status of fisheries resources in Lubuk Larangan Teluk Paman Timur, Kampar Kiri District, Kampar Regency, Riau Province, using an ecosystem approach (EAFM). This research was conducted in March-May 2024 in the Lubuk Larangan Teluk Paman Timur area. The methods used in this research are qualitative and quantitative, and respondents were selected through purposive sampling with 15 people. The indicator development model used in this study refers to indicators compiled by the Directorate of Fish Resources. Indicators for each domain were converted into composite indicators through the “flag modelling” technique. Based on the analysis, the flag status for each domain in the Lubuk Larangan area of East Uncle Bay ranges from red to green. Domains with green flags include social, governance, and stakeholders. Domains with red flags are economic. Overall, the status of fisheries resource utilization in the Lubuk Larangan Teluk Paman Timur area received a yellow flag with a score of 20,359. This indicates that fisheries management in the local ecosystem has applied the principles of sustainable fisheries but is not yet optimal. Hence, a strategic plan needs to be established to optimize or improve the condition of existing domains and indicators.